The effectiveness of brief pre-discharge smoking cessation counseling among smokers hospitalised in medical and surgical ward Hospital Universiti Sains Malaysia - Zainon, Wan Mohd Nazlee Wan (2018)
Background: Cigarettes smoking is a leading preventable cause of death worldwide and the main cause of hospitalization was due to smoking related illness. Hospitalisation provides a good environment for smoking cessation. Brief smoking cessation counseling was created as it can be delivered by healthcare professional and are not time consuming. Objectives: To determine the associated factors for nicotine dependence and association between nicotine dependence and smoking related illness. The effectiveness of brief pre- discharge Smoking Cessation counseling for hospitalised patient in Hospital Universiti Sains Malaysia was also determined. Methodology: Phase one study was a cross sectional study done to 94 patient who was admitted to medical and surgical ward HUSM. Sociodemographic data was obtained and nicotine dependence for each patient was calculated using Malay version of Fagerstrom score form. Data was analyzed using simple and multiple linear regression to know the associated factor for nicotine dependence and Simple and multiple logistic confirmatory test was done to determine association between nicotine dependence and smoking related illness. Phase two study was a randomize control trial where the same 94 patients from phase one study was randomized into intervention and control group. Intervention group (n=46) received brief intervention and pamphlet regarding stop smoking whereas control group (n=48) just receive usual care. All patients were given one month follow up to assess their readiness to change using Proscha’s transtheoretical model of change. Result was analyzed using Chi square test. Result: Response rate of the study was 98%. Sociodemographic data (age, job, income and duration of hospital stay) are not significant associated factor for nicotine dependence. There are no significant association between nicotine dependence and smoking related illness. 65% patient from intervention group had change their motivation towards smoking cessation compare with only 46% of control group who change. However, result from Chi square analysis was not significant (P=0.065). Conclusion: More variables are needed to the study associated factors of nicotine dependence. Brief counseling module may motivate precontemplation hospitalised smokers to stop smoking. However different approach may be needed to get a better result.